Логістика - Страшинська, Лариса Володимирівна (My University, 2007)
Конспект лекцій з дисципліни "Логістика" має допомогти студентам краще опанувати лекційний матеріал, поглибити вивчення теоретико-методичних основ курсу, привернути їхню увагу до основних положень тем. Synopsis of lectures on "Logistics" should help students to better learn the lecture material, deepen the study of the theoretical and methodological foundations of course, to draw their attention to the main provisions of topics.
Keywords: складські послуги; транспортування; логістичний ланцюг; логістичні операції; товарорух; warehousing services; transportation; logistic chain; logistics operations; goods movement; кафедра маркетингу